A preparation process of steel-aluminum composite plate with low vacuum surface outgassing rate
By preparing a tightly structured steel-aluminum composite plate and applying a polytetrafluoroethylene emulsion-based surface reinforcement layer coating on its surface, the problem of high surface air release rate of vacuum system materials in a vacuum environment is solved, and low vacuum surface air release rate and high corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510251604.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing vacuum system materials have a high surface air release rate under vacuum environments, which affects the performance of equipment and the wide range of application fields.
The tightly structured steel-aluminum composite plate is prepared by welding, annealing and warm rolling processes, and a surface reinforcement coating is applied to its surface. The coating consists of polytetrafluoroethylene emulsion, modified titanium nitride and aluminum nitride, etc., and a dense coating is formed by ultrasonic spraying and laser drying.
The surface air release rate of steel and aluminum composite panels in a vacuum environment is significantly reduced, and the vacuum performance and corrosion resistance of the material are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite plates and relates to a preparation process of a steel-aluminum composite plate with a low vacuum surface outgassing rate. Background Art
[0002] Steel-aluminum composite plate is a new type of material prepared by using composite technology to achieve a firm metallurgical bond between two different metals, steel plate and aluminum plate, at the interface.
[0003] Any solid material can dissolve and adsorb some gases in the atmosphere. When the material is placed in a vacuum, it will release gas due to dissolution and desorption. The study of the outgassing rate of vacuum materials has a wide range of application value in the research of satellite, spacecraft and space station pollution protection, the development of atomic clocks, the acquisition and measurement of extremely high vacuum, and the manufacturing of light sources and heat sources.
[0004] Compared with the stainless steel material commonly used in the vacuum industry as a manufacturing raw material, the steel-aluminum composite plate has the advantages of relatively low price and easy cutting of carbon steel, as well as the excellent properties of aluminum. As a vacuum system material, it can have a very low vacuum surface outgassing rate under the same vacuum degree, and has the same corrosion resistance as stainless steel. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation process for a steel-aluminum composite plate with a low vacuum surface outgassing rate. In the present invention, a steel-aluminum composite plate with a tight structure is prepared by welding, annealing, and warm rolling processes, and a surface strengthening layer coating is applied on the surface of the steel-aluminum composite plate to reduce the surface outgassing rate of the steel-aluminum plate in a vacuum environment.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A preparation process of a steel-aluminum composite plate with a low vacuum surface outgassing rate comprises the following steps: S1. Grind the steel plate and the aluminum plate by a grinder, then wash the surface of the steel plate and the aluminum plate by acid solution. After washing, blow nitrogen gas through the steel plate and the aluminum plate at 70° C. for 4 to 6 hours to obtain dry steel plate and aluminum plate; S2, placing the steel plate obtained in step S1 as the cover plate on the top and the aluminum plate as the base plate on the bottom, and preparing a steel-aluminum composite plate by welding; S3, annealing the welded steel-aluminum composite plate at 450-550°C for 15-25h, then warm rolling with a pass reduction rate of 15-20%, cooling to 200-250°C, keeping warm for 8-11h, and then naturally cooling to room temperature; S4. First, the surface of the steel-aluminum composite plate after step S3 is sandblasted, and the prepared surface strengthening layer coating raw material is evenly coated on the surface of the steel-aluminum composite plate by ultrasonic spraying, and then the low vacuum surface release rate steel-aluminum composite plate is obtained by laser drying and curing, wherein the power of the laser drying is 15-20MW, and the drying time is 25-30s. The surface strengthening layer is cured by the following components in parts by weight: 30-45 parts of polytetrafluoroethylene emulsion, 3-5 parts of dispersant, 3-5 parts of surfactant, 5-8 parts of deionized water, 5-8 parts of modified titanium nitride, and 3-5 parts of aluminum nitride, wherein the modified titanium nitride is prepared by nitriding zirconium tetrachloride, solvent and titanium source as raw materials under nitrogen.
[0007] As a preferred technical solution of the present invention, in step S1, the nitrogen gas is introduced at a flow rate of 15 m / s.
[0008] As a preferred technical solution of the present invention, in step S1, the acid solution is a hydrochloric acid aqueous solution with a mass fraction of 15%.
[0009] As a preferred technical solution of the present invention, in step S2, the specific process of welding is: placing the aluminum plate and the steel plate in a vacuum sealed environment, the welding vacuum degree is ≤1.0Pa, the steel plate is used as the cover plate on the top, and the aluminum plate is used as the base plate on the bottom, and welding is performed. The welding conditions are: under argon protection, the welding current is 80~100A, and the welding depth is 50~80mm.
[0010] As a preferred technical solution of the present invention, in step S4, the preparation method of the surface strengthening layer coating raw material is: first, the modified titanium nitride and aluminum nitride are crushed by a crusher and then passed through a 100-mesh sieve, and then the polytetrafluoroethylene emulsion and deionized water are fully stirred according to the mass fraction, and then a surfactant and a dispersant are added, and the prepared surface strengthening layer coating raw material is obtained after fully stirring.
[0011] As a preferred technical solution of the present invention, in step S4, the power of the ultrasonic spraying is 60-80 W, the ultrasonic frequency is 160-200 kHz, the continuous spraying amount is 700-1000 mL / h, and the spraying distance is 30-50 mm.
[0012] As a preferred technical solution of the present invention, in step S4, the preparation process of the modified titanium nitride is as follows: The zirconium tetrachloride, solvent and titanium source are mixed, stirred at 100-200°C for 6-9h, cooled naturally to room temperature after stirring, filtered, washed with deionized water, dried at 95-105°C for 3-5h, and the dried solid is calcined at 300-450°C for 4-6h to obtain solid A, wherein the titanium source is one of titanyl sulfate, tetraethyl titanate, tetrabutyl titanate and tetrapentyl titanate, and the solvent is one or more of methanol, ethanol, isopropanol, propylene glycol, glycerol or ether; Solid A was nitrided by introducing nitrogen into a tubular furnace at 700-900° C. for 4-7 hours, and then naturally cooled to room temperature. The solid was ball milled at a speed of 500 r / min for 3 hours to obtain the modified titanium nitride.
[0013] As a preferred technical solution of the present invention, in step S4, the dispersant is one of polyether-modified polysiloxane and hydroxyethyl cellulose.
[0014] As a preferred technical solution of the present invention, in step S4, the surfactant is an acetylene glycol surfactant.
[0015] Titanium nitride has a low secondary electron emission rate. Adding titanium nitride to the coating helps to reduce gas release in the vacuum system. In the present invention, when preparing titanium nitride, zirconium salt is added and mixed, and then calcined to obtain zirconium-containing titanium nitride. Zirconium and titanium have similar atomic sizes and similar properties, and can form a solid solution in titanium nitride, thereby improving vacuum performance.
[0016] As a fluorocarbon resin, polytetrafluoroethylene (PTFE) has excellent weather resistance, chemical resistance and sealing performance, and can effectively prevent the penetration and release of gas molecules. After adding a layer of coating on the surface of the steel-aluminum composite plate, the polytetrafluoroethylene coating itself has excellent density, which can effectively reduce the pores and defects inside the coating, thereby reducing the possibility of gas release; and the coating has stable chemical properties and is not easy to react with other substances in the vacuum environment, reducing the gas release caused by chemical reactions. The coating also has excellent weather resistance and corrosion resistance, and can resist the erosion of the coating surface by harsh environments, thereby maintaining the integrity and stability of the coating and reducing gas release.
[0017] The present invention adds aluminum nitride to the surface strengthening layer coating. Aluminum nitride has high thermal conductivity and can more effectively remove the heat inside the coating, reducing the internal gas release of the material caused by temperature increase. Aluminum nitride has stable chemical properties and is not easy to react with other substances, which helps to reduce the gas release caused by chemical reactions in a vacuum environment; aluminum nitride has good thermal shock resistance and high-temperature mechanical properties, which can enhance the overall strength and stability of the coating, thereby reducing the gas release caused by coating damage.
[0018] When preparing the steel-aluminum composite plate, the present invention first cleans the surface of the metal composite plate with acid solution to remove adsorbed impurities and gases and reduce the outgassing source, and then dries it with nitrogen; then laser welding is performed. Laser welding has the characteristics of easy manipulation of heat source and optical path and simple control, can accurately control the welding process, ensure the quality of the weld, and is conducive to maintaining the shape and dimensional stability of the composite plate.
[0019] During the laser welding process, the stirring effect of the laser beam on the molten pool can inhibit the generation of pores. During high laser power density welding, the molten pool volume is small, the cooling is fast, the precipitation time of hydrogen bubbles is short, and the bubble escape rate is greater than the bubble precipitation and growth rate, thereby obtaining a weld with low porosity.
[0020] At the same time, during the laser welding process, the heat source is concentrated and the energy is high, and the welding speed is fast, which reduces the time for the chemical reaction between the surface of the composite plate and the oxygen, nitrogen, etc. in the air, thereby reducing the gas release caused by the chemical reaction.
[0021] After welding, annealing is performed to remove welding residual stress to avoid cracking and deformation caused by stress concentration. Then, plastic deformation is performed during warm rolling to make the internal structure of the composite plate tighter and improve its density.
[0022] Beneficial effects of the present invention: In the present invention, a steel-aluminum composite plate with a tight structure is prepared by laser welding, annealing and warm rolling processes, and a surface strengthening layer coating is applied on the surface of the steel-aluminum composite plate. The coating uses polytetrafluoroethylene emulsion as a base material, and modified titanium nitride and aluminum nitride are added, combined with other additives, to form a dense coating on the surface of the steel-aluminum composite plate, thereby reducing the surface outgassing rate of the steel-aluminum composite plate in a vacuum environment. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] In the following examples and comparative examples: The aluminum plate used is 1060 aluminum plate, and the steel plate is 10# high-quality low-carbon steel plate; Polyether-modified polysiloxane: purchased from Shanghai Kelaman Reagent Co., Ltd. Polytetrafluoroethylene emulsion: purchased from Hubei Shiteng Chemical Technology Co., Ltd., product number: 0213; Tetraethyl titanate: purchased from Hubei Tosoh Chemical Technology Co., Ltd. Zirconium tetrachloride: purchased from Shanghai Myrel Biochemical Technology Co., Ltd.; Alkyne diol surfactant: purchased from Jiangsu Xinsu New Materials Co., Ltd.; Aluminum nitride: purchased from Yumu (Ningbo) New Materials Co., Ltd.
[0025] Example 1 S1. The steel plate and the aluminum plate are polished by a polishing machine, and then the surfaces of the steel plate and the aluminum plate are washed by a 15% by mass hydrochloric acid aqueous solution. After washing, nitrogen is introduced to the steel plate and the aluminum plate for 4 hours at 70° C. to obtain dry steel plate and aluminum plate, and the nitrogen introduction flow rate is 15 m / s; S2, placing the steel plate obtained in step S1 as the cover plate on the top and the aluminum plate as the base plate on the bottom, placing them in a vacuum sealed environment, and performing welding treatment, the welding vacuum degree is ≤1.0Pa, the welding conditions are: under argon protection, the welding current is 80A, the welding depth is 50mm, and a steel-aluminum composite plate is prepared by welding; S3, annealing the welded steel-aluminum composite plate at 450°C for 15h, then warm rolling with a pass reduction rate of 15%, cooling to 200°C, keeping warm for 8h, and then naturally cooling to room temperature; S4. The preparation process of modified titanium nitride is as follows: Zirconium tetrachloride, ethanol and tetraethyl titanate were mixed, stirred at 100°C for 6 hours, cooled naturally to room temperature after stirring, filtered, washed with deionized water, dried at 95°C for 3 hours, and the dried solid was calcined at 300°C for 4 hours to obtain solid A; Solid A was nitrided for 4 hours by introducing nitrogen into a tubular furnace at 700° C., and then naturally cooled to room temperature. The solid was ball milled at a speed of 500 r / min for 3 hours to prepare the modified titanium nitride.
[0026] According to weight, 5 parts of modified titanium nitride and 3 parts of aluminum nitride are first crushed by a grinder and then passed through a 100-mesh sieve, and then fully mixed with 30 parts of polytetrafluoroethylene emulsion and 5 parts of deionized water, and then 3 parts of polyether modified polysiloxane and 3 parts of acetylene glycol surfactant are added, and the prepared surface strengthening layer coating raw material is obtained after fully mixing.
[0027] First, the surface of the steel-aluminum composite plate after step S3 is sandblasted, and the prepared surface strengthening layer coating raw material is evenly coated on the surface of the steel-aluminum composite plate by ultrasonic spraying, and then the low vacuum surface degassing rate steel-aluminum composite plate is obtained by laser drying and curing, wherein the power of laser drying is 15MW, the drying time is 25s, the power of ultrasonic spraying is 60W, the ultrasonic frequency is 160kHz, the continuous spraying amount is 700mL / h, and the spraying distance is 30mm.
[0028] Example 2 S1. The steel plate and the aluminum plate are polished by a polishing machine, and then the surfaces of the steel plate and the aluminum plate are washed by a 15% by mass hydrochloric acid aqueous solution. After washing, nitrogen is introduced to the steel plate and the aluminum plate for 5 hours at 70° C. to obtain dry steel plate and aluminum plate. The nitrogen introduction flow rate is 15 m / s. S2, placing the steel plate obtained in step S1 as the cover plate on the top and the aluminum plate as the base plate on the bottom, placing them in a vacuum sealed environment, and performing welding treatment, the welding vacuum degree is ≤1.0Pa, the welding conditions are: under argon protection, the welding current is 90A, the welding depth is 70mm, and a steel-aluminum composite plate is prepared by welding; S3, annealing the welded steel-aluminum composite plate at 500°C for 20h, then warm rolling with a pass reduction rate of 18%, then cooling to 220°C, keeping warm for 9h, and then naturally cooling to room temperature; S4. The preparation process of modified titanium nitride is as follows: Zirconium tetrachloride, ethanol and tetraethyl titanate were mixed, stirred at 150°C for 7 hours, cooled naturally to room temperature after stirring, filtered, washed with deionized water, dried at 100°C for 4 hours, and the dried solid was calcined at 380°C for 5 hours to obtain solid A; Solid A was nitrided for 6 hours by introducing nitrogen into a tube furnace at 800° C., and then naturally cooled to room temperature. The solid was ball milled at a speed of 500 r / min for 3 hours to prepare the modified titanium nitride.
[0029] According to weight, 7 parts of modified titanium nitride and 4 parts of aluminum nitride are first crushed by a grinder and then passed through a 100-mesh sieve, and then fully mixed with 38 parts of polytetrafluoroethylene emulsion and 6 parts of deionized water, and then 4 parts of polyether modified polysiloxane and 4 parts of acetylene glycol surfactant are added, and the prepared surface strengthening layer coating raw material is obtained after fully mixing.
[0030] First, the surface of the steel-aluminum composite plate after step S3 is sandblasted, and the prepared surface strengthening layer coating raw material is evenly coated on the surface of the steel-aluminum composite plate by ultrasonic spraying, and then the low vacuum surface degassing rate steel-aluminum composite plate is obtained by laser drying and curing, wherein the power of laser drying is 18MW, the drying time is 28s, the power of ultrasonic spraying is 70W, the ultrasonic frequency is 180kHz, the continuous spraying amount is 800mL / h, and the spraying distance is 40mm.
[0031] Example 3 S1. The steel plate and the aluminum plate are polished by a polishing machine, and then the surfaces of the steel plate and the aluminum plate are washed by a 15% by mass hydrochloric acid aqueous solution. After washing, nitrogen is introduced to the steel plate and the aluminum plate for 6 hours at 70° C. to obtain dry steel plate and aluminum plate, and the nitrogen introduction flow rate is 15 m / s; S2, placing the steel plate obtained in step S1 as the cover plate on the top and the aluminum plate as the base plate on the bottom, placing them in a vacuum sealed environment, and performing welding treatment, the welding vacuum degree is ≤1.0Pa, the welding conditions are: under argon protection, the welding current is 100A, the welding depth is 80mm, and a steel-aluminum composite plate is prepared by welding; S3, annealing the welded steel-aluminum composite plate at 550°C for 25h, then warm rolling with a pass reduction of 20%, cooling to 250°C, keeping warm for 11h, and then naturally cooling to room temperature; S4. The preparation process of modified titanium nitride is as follows: Zirconium tetrachloride, ethanol and tetraethyl titanate were mixed, stirred at 200°C for 9 hours, cooled naturally to room temperature after stirring, filtered, washed with deionized water, dried at 105°C for 5 hours, and the dried solid was calcined at 450°C for 6 hours to obtain solid A; Solid A was nitrided for 7 hours by introducing nitrogen into a tube furnace at 900° C., and then naturally cooled to room temperature. The solid was ball milled at a speed of 500 r / min for 3 hours to prepare the modified titanium nitride.
[0032] According to weight, 8 parts of modified titanium nitride and 5 parts of aluminum nitride are first crushed by a grinder and then passed through a 100-mesh sieve, and then fully mixed with 45 parts of polytetrafluoroethylene emulsion and 8 parts of deionized water, and then 5 parts of polyether modified polysiloxane and 5 parts of acetylene glycol surfactant are added, and the prepared surface strengthening layer coating raw material is obtained after fully mixing.
[0033] First, the surface of the steel-aluminum composite plate after step S3 is sandblasted, and the prepared surface strengthening layer coating raw material is evenly coated on the surface of the steel-aluminum composite plate by ultrasonic spraying, and then the low vacuum surface degassing rate steel-aluminum composite plate is obtained by laser drying and curing, wherein the power of laser drying is 20MW, the drying time is 30s, the power of ultrasonic spraying is 80W, the ultrasonic frequency is 200kHz, the continuous spraying amount is 1000mL / h, and the spraying distance is 50mm.
[0034] Comparative Example 1 Comparative Example 1 is compared with Example 1. In step S4 of Comparative Example 1, the titanium nitride is not modified, and zirconium tetrachloride is not added, and the other operations are the same.
[0035] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, no surface strengthening layer coating is applied on the surface of the steel-aluminum composite plate, and the other operations are the same.
[0036] Performance Test: The specific process of testing the steel-aluminum composite panels prepared in Examples 1-3 and Comparative Examples 1-2 by the static pressure-increasing method is as follows: The measuring device was evacuated to the ultimate vacuum, the high vacuum chamber valve was closed, and the high vacuum constant volume chamber was evacuated to the ultimate vacuum before measurement. The pressure change was measured by a capacitance film vacuum gauge with a range of 133 Pa. The ultimate vacuum degree was 9.2 x 10 -9 P, surface outgassing rate (q) is calculated as: q = (△P*V) / (t*S) Where △P is the pressure difference, Pa; V is the volume. The volume of the sample chamber in this method is 1.17ⅹ10 -2 ; t is the time interval, which is 1800s in this method; S is the surface area of the steel-aluminum composite plate, 100cm 2 .
[0037] Repeat the experiment 6 times according to the above experimental process and calculate the average value to obtain the surface outgassing rate of the high vacuum chamber:
[0038] According to the above data, it can be seen that the steel-aluminum composite plate prepared in the present invention has a lower surface outgassing rate under vacuum conditions.
[0039] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for preparing a steel-aluminum composite plate with low vacuum surface outgassing rate, characterized in that: The following steps are involved: S1. Grind the steel plate and the aluminum plate by a grinder, then wash the surface of the steel plate and the aluminum plate by acid solution. After washing, blow nitrogen gas through the steel plate and the aluminum plate at 70° C. for 4 to 6 hours to obtain dry steel plate and aluminum plate; S2, placing the steel plate obtained in step S1 as the cover plate on the top and the aluminum plate as the base plate on the bottom, and preparing a steel-aluminum composite plate by welding; S3, annealing the welded steel-aluminum composite plate at 450-550°C for 15-25h, then warm rolling with a pass reduction rate of 15-20%, cooling to 200-250°C, keeping warm for 8-11h, and then naturally cooling to room temperature; S4. First, the surface of the steel-aluminum composite plate after step S3 is sandblasted, and the prepared surface strengthening layer coating raw material is evenly coated on the surface of the steel-aluminum composite plate by ultrasonic spraying, and then the low vacuum surface release rate steel-aluminum composite plate is obtained by laser drying and curing, wherein the power of the laser drying is 15-20MW, and the drying time is 25-30s. The surface strengthening layer is cured by the following components in parts by weight: 30-45 parts of polytetrafluoroethylene emulsion, 3-5 parts of dispersant, 3-5 parts of surfactant, 5-8 parts of deionized water, 5-8 parts of modified titanium nitride, and 3-5 parts of aluminum nitride, wherein the modified titanium nitride is prepared by nitriding zirconium tetrachloride, solvent and titanium source as raw materials under nitrogen.
2. The process for preparing the steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S1, the nitrogen gas is introduced at a flow rate of 15 m / s.
3. The process for preparing the steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S1, the acid solution is a hydrochloric acid aqueous solution with a mass fraction of 15%.
4. The process for preparing the steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S2, the specific process of welding is: placing the aluminum plate and the steel plate in a vacuum sealed environment, the welding vacuum degree is ≤1.0Pa, the steel plate is used as the cover plate on the top, and the aluminum plate is used as the base plate on the bottom, and welding is performed. The welding conditions are: under argon protection, the welding current is 80~100A, and the welding depth is 50~80mm.
5. The process for preparing the steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S4, the preparation method of the surface strengthening layer coating raw material is: first, according to the mass fraction, the modified titanium nitride and aluminum nitride are crushed by a crusher and then passed through a 100-mesh sieve, and then fully stirred with polytetrafluoroethylene emulsion and deionized water, and then a surfactant and a dispersant are added, and the prepared surface strengthening layer coating raw material is obtained after fully stirring.
6. The process for preparing a steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S4, the power of the ultrasonic spraying is 60-80 W, the ultrasonic frequency is 160-200 kHz, the continuous spraying amount is 700-1000 mL / h, and the spraying distance is 30-50 mm.
7. The process for preparing a steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S4, the preparation process of the modified titanium nitride is as follows: The zirconium tetrachloride, solvent and titanium source are mixed, stirred at 100-200°C for 6-9h, cooled naturally to room temperature after stirring, filtered, washed with deionized water, dried at 95-105°C for 3-5h, and the dried solid is calcined at 300-450°C for 4-6h to obtain solid A, wherein the titanium source is one of titanyl sulfate, tetraethyl titanate, tetrabutyl titanate and tetrapentyl titanate, and the solvent is one or more of methanol, ethanol, isopropanol, propylene glycol, glycerol or ether; Solid A was nitrided by introducing nitrogen into a tubular furnace at 700-900° C. for 4-7 hours, and then naturally cooled to room temperature. The solid was ball milled at a speed of 500 r / min for 3 hours to obtain the modified titanium nitride.
8. The process for preparing a steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S4, the dispersant is one of polyether-modified polysiloxane and hydroxyethyl cellulose.
9. The process for preparing a steel-aluminum composite plate with low vacuum surface outgassing rate according to claim 1, characterized in that: In step S4, the surfactant is an acetylene glycol surfactant.
Citation Information
Patent Citations
Production method for layered wearproof lightweight steel-aluminum composite boards
CN103878536A
Steel-aluminum composite steel and machining method thereof
CN110900114A
High surface area metal nitrides or metal oxynitrides for electrical energy storage
CN1240049A
Ni-P composite coating contg. silicon carbide and PTFE
CN1451782A
Composition of coating for Anti-corrosion treatment of submersible pump
KR101843392B1